2016
DOI: 10.3923/rjmp.2016.79.88
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Effect of Anthocleista vogelii Ethanolic Root Extract in Alloxan-Induced Diabetic Rats

Abstract: This study was carried out to evaluate the potential anti-diabetic effect of Anthocleista vogelii ethanolic root extract in alloxan-induced diabetic rats. Albino rats of both sexes were randomly divided into five groups with five rats each. Group 1 (control; 10 mL kgG 1 distilled water), group 2-4 (100, 200 and 400 mg kgG 1 A. vogelii ethanolic root extract) and group 5 (5 mg kgG 1 glibenclamide). Diabetes was induced physiologically using 10 g kgG 1 glucose p.o. and chemically using 150 mg kgG 1 alloxan i.p. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…However, our study showed that prolonged treatment with CF at doses above 100 mg/kg bw may lead to hypoglycemic condition. Findings of this study corroborate previous reports of the glucose lowering actions of A. vogelii extracts and fractions in diabetic rats (Osadebe et al, 2014;Sunday et al, 2016;Onyekere et al, 2017) and obese rats (Anyanwu et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…However, our study showed that prolonged treatment with CF at doses above 100 mg/kg bw may lead to hypoglycemic condition. Findings of this study corroborate previous reports of the glucose lowering actions of A. vogelii extracts and fractions in diabetic rats (Osadebe et al, 2014;Sunday et al, 2016;Onyekere et al, 2017) and obese rats (Anyanwu et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Numerous research works have been done over the years to determine the biological activities of different solvent extracts of Anthocleista vogelii. These previous studies reported that Anthocleista vogelii exerted analgesic, antidiabetic [13,14] , anti-plasmodial [24] , antibacterial [25] and anti-fungal [26] effects. Earlier research works reported that some plants exert therapeutic properties which include analgesic [27] , anti-inflammatory [28] , anticancer [29,30] and antidiabetic [15,31] effect due to their antixodant activities.…”
Section: Discussionmentioning
confidence: 99%
“…Anthocleista vogelii belonging to the family Loganiaceae is a plant used in ethno-medicine for the treatment of various diseases which includes fever, syphilis, pile and stomach ache [11,12] . Previous studies reported that Anthocleista vogelii root exerted antidiabetic effect in albino rats that were induced with diabetes using streptozocin and alloxan [13,14] . Previous studies also reported the presence of phenolic content and antioxidant property of Anthocleista vogelii root [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The stem bark and leaf extracts of A. vogelii are used to treat malaria, diabetes, microbial infections, hypertension, rheumatism, fever, jaundice, and an ulcer (Alaribe et al, 2012;Anyanwu et al, 2013). The stem bark has also been reported to possess antidiabetic, antiulcerogenic, antiobesity, anti-infertility, antibiotic, and hepatoprotective properties (Oladimeji et al, 2014;Osadebe et al, 2014;Sunday et al, 2016;Chukwu et al, 2020). This study was therefore designed to investigate the renal protective and lipid profile modulatory effects of ethanol extract of A. vogelii stem bark (EASB) on rats induced renal injury with CCl4induction.…”
Section: Introductionmentioning
confidence: 99%